PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) UNTUK LEGALITAS HUKUM PADA UMKM DI DESA SINE KABUPATEN NGAWI - Muttaqin, Muttaqin; Kasanah, Miftakul Nurul; Purwaningsih, Yuliani; Suchahyadin, Hasan; Puspitasari, Niken Siti; Musfiroh, Ririn; Hartaningrum, Trining Galuh; Handayani, Putri Dewi; Sayekti, Mahendhi Pasca Ayu; Sidiq, Akbar A.; Maskhur, Mohammad Ali; Anam, Ruzig Khoirul; Muhamad, Trio Okta; Haniiah, Ni'matul; Kusumastuti, Qodriyana; Ma'rufi, Rosyidi Agus; Puspawardani, Novita Andriana (Abdimas IAI Ngawi, 2024)
Community Service Program (PPM) of the Institute of Islamic Religion (IAI) Ngawi focuses on making a Business Identification Number (NIB) for Micro, Small and Medium Enterprises (MSMEs) in Sine Village. Micro, Small, and Medium Enterprises (MSMEs) in Sine Village. NIB is a legal identity that provides formal legality to the business, enabling access to various business licenses, legal protection, as well as support and assistance. licenses, legal protection, and government assistance and facilities. This program aims to facilitate MSMEs in the NIB registration process through the Online Single Submission (OSS) platform. In the implementation of the program, IAI Ngawi PPM team provides assistance in making NIB and provides education on the benefits and procedures for NIB registration. about the benefits and procedures for NIB registration. This process includes filling in data online, verification, and issuance of NIB which takes place efficiently and quickly. fast. This program provides significant impact by improving business legality, expanding MSMEs' access to government support, and strengthening their credibility in the eyes of the government. access to government support, and strengthening business credibility in the eyes of consumers. consumers. It is expected that the program will continue and become a catalyst for the development of MSMEs in Sine Village, supporting local economic growth and for the development of MSMEs in Sine Village, supporting local economic growth and creating new opportunities. creating new opportunities. Keywords: Community Service, Business Identification Number (NIB), MSME.   Abstrak: Program Pengabdian Pada Masyarakat (PPM) Institut Agama Islam (IAI) Ngawi menitikberatkan pada pembuatan Nomor Induk Berusaha (NIB) untuk pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Sine. NIB adalah identitas hukum yang memberikan legalitas formal kepada usaha, memungkinkan akses ke berbagai izin usaha, perlindungan hukum, serta bantuan dan fasilitas pemerintah. Program ini bertujuan untuk mempermudah UMKM dalam proses pendaftaran NIB melalui platform Online Single Submission (OSS). Dalam pelaksanaan program, tim PPM IAI Ngawi melakukan pendampingan pembuatan NIB dan memberikan edukasi mengenai manfaat dan prosedur pendaftaran NIB. Proses ini mencakup pengisian data secara online, verifikasi, dan penerbitan NIB yang berlangsung efisien dan cepat. Program ini memberikan dampak signifikan dengan meningkatkan legalitas usaha, memperluas akses UMKM terhadap dukungan pemerintah, serta memperkuat kredibilitas usaha di mata konsumen. Diharapkan, program ini akan terus berlanjut dan menjadi katalisator bagi pengembangan UMKM di Desa Sine, mendukung pertumbuhan ekonomi lokal dan menciptakan peluang baru. Kata Kunci: Pengabdian pada masyarakat, Nomor Induk Berusaha (NIB), UMKM